Enhancing Human Resource Quality and Strengthening Strategies for Tourism Development in East Nusa Tenggara, Indonesia - Putranto, Diyan; Astuti, Marhanani Tri; Halawa , Fransiscus Amonio (Indonesian Scientific Publication, 2025)
This study examines the quality and development of human resources (HR) in the tourism sector of East Nusa Tenggara (NTT), Indonesia, an emerging destination with significant natural and cultural assets but persistent workforce challenges. Using a mixed-methods approach across five key destinations—Komodo, Kelimutu, Alor, Rote, and Sumba—the research assesses HR competencies, certification, training access, digital and language skills, and stakeholder collaboration. Findings reveal that fewer than 13% of tourism workers hold industry-recognized certifications, vocational training is unevenly distributed, and digital and language skills remain limited, particularly in rural and remote areas. Socio-cultural barriers, fragmented stakeholder collaboration, and infrastructural constraints further hinder effective HR development. The study highlights the need for context-specific strategies, including localized vocational curricula, subsidized and mobile certification programs, digital upskilling, and inclusive, multi-stakeholder governance frameworks. Real-life examples from Komodo National Park and Bali’s community-based tourism illustrate both the potential and challenges of integrated HR development. Recommendations emphasize reforming education and training, expanding certification, fostering digital literacy, and strengthening institutional collaboration to build a competitive and sustainable tourism workforce in NTT. The research provides actionable insights for policymakers and stakeholders aiming to elevate NTT’s tourism sector through targeted human capital enhancement.